2019
DOI: 10.1021/acs.jpcc.9b01335
|View full text |Cite
|
Sign up to set email alerts
|

Doping Effects on the Reactivity of the MVO5 (M = V–Zn) Clusters in CO Oxidation Reaction

Abstract: Doped metal oxide catalysts have important applications in heterogeneous catalysis, whereas the fundamental effects of doping on the reactivity of catalysts are elusive. Herein, benefiting from the study of a series of atomic clusters MVO 5 − (M = V−Zn) in catalytic CO oxidation by molecular O 2 under thermal collision conditions, the crucial effects of doping on the electronic structure and then the catalytic reactivity of MVO 5 − were successfully rationalized by using mass spectrometry and theoretical calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 68 publications
0
11
0
1
Order By: Relevance
“…While band structure models are commonly available or readily calculated -both analytical and numerically computed -it is generally more challenging to accurately capture the scattering time. Rigorously resolving the relaxation time τ (k) over the entire Brillouin zone is possible [8,[10][11][12][13][14][15][16][34][35][36][37][38][39], but computationally expensive, thus various approximations are commonly adopted. One of the most widespread approximations involves setting the scattering time to a constant, τ (k) = τ 0 (TAU model).…”
Section: Theoretical Approachmentioning
confidence: 99%
See 3 more Smart Citations
“…While band structure models are commonly available or readily calculated -both analytical and numerically computed -it is generally more challenging to accurately capture the scattering time. Rigorously resolving the relaxation time τ (k) over the entire Brillouin zone is possible [8,[10][11][12][13][14][15][16][34][35][36][37][38][39], but computationally expensive, thus various approximations are commonly adopted. One of the most widespread approximations involves setting the scattering time to a constant, τ (k) = τ 0 (TAU model).…”
Section: Theoretical Approachmentioning
confidence: 99%
“…Rigorous first-principles calculations of electronphonon scattering have shown that often the scattering rates are (roughly) proportional to the electron DOS, D(E) [10,16,38,39]. Intuitively, one would expect the probability of scattering to scale with the number of available final states, which partially explains this trend.…”
Section: Theoretical Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Our rigorous el-ph scattering calculations show that, in the case of GeTe, both the scattering rates and MFP are energy-dependent. An alternative simple model, that appears to work well, assumes the scattering rate is proportional to the electron DOS [49,50].…”
Section: Electron-phonon Scattering Rates and Mean-free-pathsmentioning
confidence: 99%